HASIL BELAJAR FISIKA SISWA MELALUI PENDEKATAN MULTI KECERDASAN DENGAN MENGGUNAKAN PETA KONSEP DI KELAS X8 SMAN I PANGKALAN KERINCI - Darwin Darwin; Azizahwati Azizahwati; Deliana Sagala (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The purpose of this research was to find the student physics learning achievement as topic rectilinear motion kinematic through Multi Intelligences approach implementation by using Concept Map. The subject of the research was the students of X8 Class of SMA I Pangkalan Kerinci in the academic year 2005/2006 the sample was taken was 35 students. The instrument of collecting data was a test of learning achievement used descriptive analysis which consists of digestibility, the effectiveness of learning, the student completeness learning, the completeness indicators, the affective evaluation, and psychomotor evaluation. The finding showed that the average of students' digestibility is 80,8% categorized well. The effectiveness of learning is 80,8% with the completeness indicator is 92%. The effective evaluation is categorized good enough (57,1%) and the psychomotor evaluation is categorized very good (62,8%).